Complete mitochondrial genome of the parrotfish Calotomus japonicus (Osteichthyes: Scaridae) with implications based on the phylogenetic position - Mabuchi, Kohji (Mitochondrial DNA B Resour, 2016)
The complete mitochondrial genome sequence was determined for a specimen of Calotomus japonicus, a temperate parrotfish endemic to coastal East Asia. It was compared phylogenetically with previously published partial sequences from this species and other parrotfishes. The obtained tree indicated that the three cytb sequences of C. japonicus from a recent molecular study (LC068806-8) probably resulted from introgression through intergeneric hybridization, or possibly from sample confusion. Taking the presently obtained mitogenome as representative of C. japonicus, the species most closely related to this one among congeners is C. zonarchus, which is endemic to the Hawaiian islands.